Chronic Postsurgical Pain Outcomes in Breast Reconstruction Patients Receiving Perioperative Transversus Abdominis Plane Catheters at the Donor Site: A Prospective Cohort Follow‐up Study. Issue 8 (23rd February 2017) - Oh, Justin; Pagé, M. Gabrielle; Zhong, Toni; McCluskey, Stuart; Srinivas, Coimbatore; O'Neill, Anne C.; Kahn, James; Katz, Joel; Hofer, Stefan O.P.; Clarke, Hance
Abstract: Background: Chronic postsurgical pain (CPSP) is a debilitating and costly condition. Risk factors for CPSP after autologous breast reconstruction have not been clearly established. Previously, we demonstrated that transversus abdominis plane (TAP) catheters delivering intermittent local anesthetic reduced postoperative morphine consumption. This prospective follow‐up study aimed to (1) compare the incidence of CPSP after autologous breast reconstruction between patients who received postoperative intermittent TAP catheters with bupivacaine or saline boluses and (2) assess the factors that contribute to the development and maintenance of CPSP in this study cohort. Methods: Ninety‐three patients who underwent deep inferior epigastric artery perforator or muscle‐sparing transverse rectus abdominis breast reconstruction were randomized to receive TAP catheters with bupivacaine or saline postoperatively. Subsequently, patients were followed for a year to assess persistent pain, pain severity, quality of life scores, and functional disability at 6 and 12 months after surgery. Results: Twenty‐four percent and 23% of patients reported CPSP at 6 and 12 months, respectively. There were no significant differences between groups (bupivacaine vs. placebo) on pain‐related variables, including incidence of CPSP. Patients who reported greater variability in pain scores at rest over the first 48 hours postoperatively were more likely to have CPSP 6 months, but not 12 months, later. Conclusions: Acute postoperative pain variability may contribute to the development of CPSP up to 6 months after autologous breast reconstruction surgery. Neither postoperative use of bupivacaine vs. saline in the TAP catheters nor acute pain severity influenced the 6‐ or 12‐month incidence of CPSP.